Progress in Intelligent Computing Techniques : Theory, Practice, and Applications : Proceedings of ICACNI 2016, Volume 2 /: Theory, Practice, and Applications : Proceedings of ICACNI 2016, Volume 2. (2017) - Unknown
No abstract available